Ukuran Panjang Total Ikan Kerapu Hasil Tangkapan Nelayan Simeulue - Irja, Mhd.; Hermi, Rudi; Edwarsyah, Edwarsyah; Heriansyah, Heriansyah; Lubis, Friyuanita; Nasution, Muhammad Arif; Rizal, Muhammad (Universitas Teuku Umar, 2024)
Grouper is a type of fish that has economic value, thus encouraging fishermen to continue exploiting it regardless of its size. Total length research on three grouper species Plectropomus leopardus, Variola louti and Variola albimarginata was conducted in Simeulue Regency with the aim of analyzing frequency distribution. Data were collected from early January to early February 2024. The collected data were analyzed using Microsoft Excel, and displayed in graphical form. The results showed that the type of Plectropomus leopardus has a size between 16-64 cm, the largest number of sizes is 34-39 cm with a total of 122 individuals. Grouper Variola louti with a total length between 20-55 cm, size 28-31 cm is the largest total length size of 173 individuals. While grouper Variola albimarginata has a size between 16-58 cm, 298 individuals of which have a size of 26-30 cm. From this study, it can be concluded that the groupers recorded are predominantly female.